Self-Determined Motivation and Competitive Anxiety in Athletes/Students: A Probabilistic Study Using Bayesian Networks - Ponseti, Francisco Javier; Almeida, Pedro L.; Lameiras, Joao; Martins, Bruno; Olmedilla, Aurelio; López-Walle, Jeanette; Reyes, Orlando; Garcia-Mas, Alexandre (Frontiers in Psychology, 2019)
This study attempts to analyse the relationship between two key psychological variables associated with performance in sports - Self-Determined Motivation and Competitive Anxiety - through Bayesian Networks analysis. We analysed 674 university students/athletes from 44 universities that competed at the University Games in México, with an average age of 21 years (SD = 2.07) and with a mean of 8.61 years’ (SD = 5.15) experience in sports. Methods: Regarding the data analysis, first a CHAID algorithm was carried out to determine the dependence links between variables, and then a Bayesian networks was developed. The validation of the BN revealed AUC values ranging from 0.5 to 0.92. Subsequently, various instantiations were performed with hypothetical values applied to the “bottom” variables. Results showed two probability trees that have extrinsic motivation and amotivation at the top, while the anxiety/activation due to worries about performance was at the bottom of the probabilities. The instantiations carried out support the existence of these probabilistic relationships, demonstrating their scarce influence on anxiety about competition generated by the intrinsic motivation, and the complex probabilistic effect of introjected and identified regulation regarding the appearance of anxiety due to worry about performance.